Analysis of Sound Corporate Governance Effect on Company's Financial Fundamentals toward Stock Returns - Ibnu, Muhammad (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This research is proxied by Current Ratio to determine the company's ability to meet its short-term obligations through Return Shares, and Corporate Governance is expected to function as a tool to provide confidence to investors. There fore this study aims to examine and analyze the effect of Liquidity, Profitability, Solvency, Accounting Profit, and Operating Cash Flow on Return Share with Corporate Governance. To answer the above objectives, quantitative analysis is needed, with data collection methods collected through literature studies originating from books, journals, theses, the internet and documentation. Testing the hypothesis used in this study is multiple regression analysis and moderation regression analysis. The population of this study are mining sector companies listed on the Indonesia Stock Exchange. The number of companies that are the sample is 32 companies. This research uses the method purposive sampling, so that the total sample is 160 samples. The results of the study show that Profitability, Accounting Profit, and Operating Cash Flow have an effect on Return Share. While Liquidity and Solvability have no effect on Return Shares.